Consequences of Oxidative Stress on Plant Glycolytic and Respiratory Metabolism - Dumont, Sébastien; Rivoal, Jean (Frontiers in Plant Science, 2019)
Reactive oxygen species (ROS) and reactive nitrogen species (RNS) are present at low and controlled levels under normal conditions. These reactive molecules can increase to high levels under various biotic and abiotic conditions, resulting in perturbation of the cellular redox state that can ultimately lead to oxidative or nitrosative stress. In this review, we analyze the various effects that result from alterations of redox homeostasis on plant glycolytic pathway and tricarboxylic acid (TCA) cycle. Most documented modifications caused by ROS or RNS are due to the presence of redox-sensitive cysteine thiol groups in proteins. Redox modifications include Cys oxidation, disulfide bond formation, S-glutathionylation, S-nitrosylation and S-sulfhydration. A growing number of proteomic surveys and biochemical studies document the occurrence of ROS- or RNS-mediated modification in enzymes of glycolysis and the TCA cycle. In a few cases, these modifications have been shown to affect enzyme activity, suggesting an operational regulatory mechanism in vivo. Further changes induced by oxidative stress conditions include the proposed redox-dependent modifications in the subcellular distribution of a putative redox sensor, NAD-glyceraldehyde-3P dehydrogenase and the micro-compartmentation of cytosolic glycolytic enzymes. Data from the literature indicate that oxidative stress may induce complex changes in metabolite pools in central carbon metabolism. This information is discussed in the context of our understanding of plant metabolic response to oxidative stress.